Performance driven outcomes—the case of frontline employees in the hospitality sector. Issue 1 (2nd January 2019) - Prentice, Catherine; Ma, Erdan; Wong, IpKin Anthony
ABSTRACT: This study proposes a linear relationship between employee performance, job satisfaction and organizational commitment in the hospitality industry. Employees' sense of achievement intervenes in the relationship between employee performance and satisfaction. In particular, this study models service climate as a cross-level moderator in this chain relationship. The data were collected at 27 casino hotels in Macau. The study finds that job performance has significant direct and indirect effects on job satisfaction. Employees' sense of achievement significantly intervenes in the relationship between job performance and satisfaction. Service climate has significant cross-level direct and moderating effects on employee sense of achievement, job satisfaction, and organizational commitment. The study provides a fresh look into the relationship between employee performance, sense of achievement, job satisfaction and organizational commitment in the case of hospitality industry.